Fusion of multiple impacted supernumerary teeth with maxillary third molar - A rare case report - Rita Rai; Sameer Kaura; Shailza Bhardwaj; Gagandeep Satia; Namita Budhiraja (Wolters Kluwer Medknow Publications, 2021)
Fused supernumerary teeth are an uncommon finding. Fusion is an abnormality of tooth development. It is common in the lower anterior but rare in maxilla. Supernumerary teeth are additional teeth in normal series, occurring with a frequency of 0.3%-3.8% in population. The frequency of fusion of a permanent tooth with a supernumerary is <1% of cases and usually involves maxillary anterior teeth. Panoramic radiograph revealed a radiopaque mass in periapical region associated with maxillary third molar. The findings were suggestive of impacted supernumerary teeth. This case is an example of a rare phenomenon of fused multiple impacted supernumerary teeth in maxillary third molar area.